Um framework gamificado para a disciplina algoritmos ou equivalente - QUARESMA, José Augusto de Sena (Universidade Federal do Pará, 2020)
A framework gamified is our product proposal for the teaching and learning process of the Algorithms or equivalent discipline. The curricular component in question is fundamental for the courses in the area of information technology, since it bases the student and professional future on the knowledge of software development. However, we observed a high level of student disapproval and avoidance in this discipline, through consultations in the literature and at the Faculty of Computer Science of the Federal University of Pará (UFPA). From this context, the study proposes the following question-focus: How to use a strategy to get the process of teaching and learning of studied content Algorithms or systems of information undergraduation? Anchored in the question-focus has as general objective the conception of a framework gamified for the discipline Algorithms or equivalent. As a way to reach the objectives outlined, a mixed research methodology was defined, covering systematic review of the literature; survey; participant observation; peer review; and validation by means of the comparison of the acquired grades in the gamified processes and the traditionally adopted in the discipline. The data from the research allowed to contemplate the literature on the subject, the perception of the Brazilian panorama about the discipline, the teacher and student view and the observation of the teacher, student, monitor and content interaction in the UFPA reality. Through the results achieved, the product of this master's thesis with the homogeneous data structure contents was designed, designed and tested, pointing to the reality of application as the most difficult to learn by the students and teaching by the teachers. Therefore, through the experiment, corroborated by the Systematic Review of Literature, when comparing the gamified approach, to what has been used in the Algorithms of the courses of the Faculty of Computation of UFPA, we identified: (i) greater participation of students in the classroom; (ii) greater collaboration among students during the resolution of the challenges; (iii) greater engagement in resolving the lists of exercises; (iv) improvement in students' performance regarding the assessment grade; (v) use of dynamic and playful classroom practices; (vi) timely feedback on students' progress in the discipline; (vii) acceptance of the approach by students; (viii) the need to discuss the limits of gamification in the face of the occurrence of students with disabilities or of introverted temperament. With these results, we evaluated how timely and important it is to spread the teaching and learning process of the Algorithms or equivalent discipline, to help minimize the failure and avoidance rates in the discipline.